Randomised clinical trial of an early palliative care intervention (SUPPORT) for patients with idiopathic pulmonary fibrosis (IPF) and their caregivers: protocol and key design considerations. Issue 1 (19th February 2018) - Lindell, Kathleen Oare; Nouraie, Mehdi; Klesen, Melinda J; Klein, Sara; Gibson, Kevin F; Kass, Daniel J; Rosenzweig, Margaret Quinn
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF), a progressive life-limiting lung disease affects approximately 128 000 newly diagnosed individuals in the USA annually. IPF, a disease of ageing associated with intense medical and financial burden, is expected to grow in incidence globally. Median survival from diagnosis is 3.8 years, and many of these patients succumb to a rapid death within 6 months. Despite the fatal prognosis, we have found that patients and caregivers often fail to understand the poor prognosis as the disease relentlessly progresses. Based on feedback from patients and families living with IPF, we developed the S-Symptom Management, U-Understanding the Disease, P-Pulmonary Rehabilitation, P-Palliative Care, O-Oxygen Therapy, R-Research Considerations and T-Transplantation ('SUPPORT') intervention to increase knowledge of the disease, teach self-management strategies and facilitate preparedness with end of life (EOL) planning. Methods: This study is a randomised trial to test the efficacy of SUPPORT intervention compared with routine care in patients with IPF and their caregivers delivered after three clinical visits. We are recruiting a cohort of 64 new IPF patient/caregiver dyads (32 for each dyad). Results: The trial will evaluate whether the SUPPORT intervention decreases stress, improves symptom burden, quality of life, preparedness and advance care planning for patients and caregivers, quality of dying and death for caregivers if the patient dies during the course of the study, as well as assess the impact of primary palliative care on healthcare resource use near the EOL. Conclusion: By increasing knowledge of the disease, teaching self-management strategies and facilitating preparedness with EOL planning, we will address a critical gap in the care of patients with IPF. Trial registration number: NCT02929017; Pre-results.